Myocardial beta adrenoceptors and left ventricular function in hypertrophic cardiomyopathy. - Choudhury, L. (1996)
OBJECTIVE--To assess the relation between left ventricular function and myocardial beta adrenoceptor density. METHODS--17 patients with hypertrophic cardiomyopathy, six with and 11 without heart failure, were studied. Left ventricular function was assessed by echocardiography, and myocardial beta adrenoceptors by positron emission tomography. Patient data were compared with those obtained in normal controls. RESULTS--Myocardial beta adrenoceptor density in the 17 patients was 7.00 (SD 1.90) pmol/g v 11.50 (2.18) pmol/g in normal controls (P < 0.01). beta Adrenoceptor density in the six patients with left ventricular failure was 5.61 (0.88) pmol/g v 7.71 (1.86) pmol/g in the 11 patients with normal ventricular function (P < 0.05), and there was a significant correlation (r = 0.52; P < 0.05) between left ventricular fractional shortening and myocardial beta adrenoceptor density. A positive correlation (r = 0.51; P < 0.05) was also found between myocardial beta adrenoceptor density and the E/A transmitral flow ratio, an index of left ventricular diastolic function. CONCLUSIONS--There is myocardial beta adrenoceptor downregulation in patients with hypertrophic cardiomyopathy with or without signs of heart failure.